Toxicity Sub chronic Water Extract Meretrix meretrix Linnaeus In Vivo on Sprague dawley Rats - Azwin Apriandi; Kustiariyah Tarman; Purwantiningsih Sugita (Jurnal Pengolahan Hasil Perikanan Indonesia, 2016)
Meretrix meretrix is one of the shells of sea water are widely utilized by people as food. This clamalso has many properties and benefits, so in this study tested the effect of the water extract of Meretrixmeretrix against blood chemistry profile Sprague Dawley rats with the method (OECD 413: 2009). Based onobservations obtained growth, feed intake, weight of liver and kidney in normal conditions. Levels of urea,creatinine, cholesterol between the control mice treated with A/0.1 and A/1 were not significantly different(p> 0.05) while the levels of bilirubin and albumin between control mice treated with A/0.1 and A/1 resultssignificantly different (p<0.05), but all blood chemistry parameters tested is still in the normal category.